2003
DOI: 10.1021/ac0346609
|View full text |Cite
|
Sign up to set email alerts
|

Biosensing Based on Light Absorption of Nanoscaled Gold and Silver Particles

Abstract: The absorption spectrum of noble metal spherical nanoparticles is known to be strongly influenced by the dielectric constant of the surrounding material, and as such, these particles are well suited for biosensing applications. To perform biosensing using nanoparticles on a substrate, the metal particles are covalently attached onto quartz using an organic adhesion layer of mercaptosilanes. The particles in solution are characterized by UV-vis spectroscopy and transmission electron microscopy, while those atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
217
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(233 citation statements)
references
References 18 publications
12
217
1
3
Order By: Relevance
“…The shifting of wavelength could be due to the change of index of refraction around the Ag NPs induced by both JEV antibodies and BSA (Sharma et al 2012), which also indicated successful immobilization of JEV antibody onto the Ag NPs-based sensing probe (El-Sayed et al 2005). The binding of JEV antigen onto antibody immobilized Ag NPs-based sensing probes had further enhanced the intensity of surface plasmon resonance absorption at the wavelength of 427 nm (Figure 6d) (Frederix et al 2003).…”
Section: Characterization Of Ag Nps-based Sensing Probesmentioning
confidence: 86%
“…The shifting of wavelength could be due to the change of index of refraction around the Ag NPs induced by both JEV antibodies and BSA (Sharma et al 2012), which also indicated successful immobilization of JEV antibody onto the Ag NPs-based sensing probe (El-Sayed et al 2005). The binding of JEV antigen onto antibody immobilized Ag NPs-based sensing probes had further enhanced the intensity of surface plasmon resonance absorption at the wavelength of 427 nm (Figure 6d) (Frederix et al 2003).…”
Section: Characterization Of Ag Nps-based Sensing Probesmentioning
confidence: 86%
“…The formation of the complex is evidenced from the color change (detectable by human eye) and the appearance of a peak at around 770 nm (Barman et al 2014a, b;Li et al 2013;Frederix et al 2003 , though no precipitation occurred, but they could not produce any significant color change and thus no change in the UV-Visible absorption spectrum (Fig. 2C).…”
Section: Optimization Of Synthesized Agnpmentioning
confidence: 97%
“…Our results showed that the intensity of SP band of gold was increased after the exposure of biotin-functionalized gold nanoisland films to streptavidin solution (100 µg/mL) in PBS for 2 min (Figure 6). 47 No further changes were observed from the longer exposure of island films to streptavidin solution. In comparison, non-specific binding studies using MUA-functionalized gold nanoisland films showed no such change on the intensity of SP band of gold.…”
Section: Formation and Characterization Of Gold Nanoisland Filmsmentioning
confidence: 98%